PEASANTS AND GLOBALIZATION IN LATIN AMERICA: A SURVEY OF RECENT LITERATURE (REVISTA NERA, 2012)
This review essay examines trends in the multinational literature of books published on the theme of peasants and globalization in Latin America between 1990 and 2001 and cataloged by the Library of Congress. It organizes the literature by countries covered as well as by theoretical approaches. It demonstrates the influence of contending paradigms regarding the future of peasantries and argues that most books defend the notion that globalization has not eliminated but actually helped strengthen peasant survival.